The principle of secularity in the Republic of Serbia according to the Constitution of 2006 - Mitrović Petar (Anali Pravnog Fakulteta u Beogradu)
The main goal of this paper is to offer an analysis of the principle of secularity according to the Constitution of 2006, and, within it, the author proposes arguments in favor of the thesis that current Constitution accepts the model of strict separation of state and church. The paper also focuses on the questions of the great importance for state-church relations: funding of churches and religious communities from the budget, religious rituals in public bodies and institutions, the role of traditional churches and religious communities in public education system, and gives the opinion on their constitutionality in constitutional system of the Republic of Serbia.